GAMBARAN SIKAP ERGONOMI DAN PROPORSI KELUHAN MUSKULOSKELETAL PADA TENAGA KERJA BONGKAT MUAT DI PELABUHAN BONGKAR MUAT BARANG JALAN TANJUNG BATU KECAMATAN LIMA PULUH KOTA PEKANBARU - Muhammad Zulfikar hsn Ihsan; Suyanto "; Laode Burhanuddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTErgonomics deals with optimization, efficiency, health, safety, and comfort in the workplace. One of this ergonomics principle approach is important for unloading workers in the harbour, because their workplace and work-system have high risk of workplace accidents if the principles of ergonomics is not applied. So, the effectivity, efficiency, productivity, comfort, and health of workers in the harbour need to be maintained and improved with ergonomics approach. The bad application of ergonomics when work (lifting methods, the weight limit of lifted load, special technique of lifting) can affect the work stress and excessive work stress will cause musculosceletal fatigue. This research was held on H. Ali Akbar unloading harbour on Jl. Tanjung Batu, Lima Puluh, Pekanbaru, with descriptive observasional method to describe risk of work ergonomy caused by bad application of ergonomics at work and musculosceletal symptoms proportion of 19 unloading workers by Nordic Body Map (NBM) questionnaire. The result is all unloading workers (100%) have musculosceletal injury with various grade of injury. When being observed, none of all unloading workers lift the load with the right method and no special technique had been used by unloading workers to lift the load.Keywords : ergonomy, musculosceletal injury, occupational disease